G527(P) Neonatal readmission rates: an audit of current practice. (25th October 2020) - Seed, R; Cullen, T; Rajaram, J
Abstract : Aims: To identify the rate at which neonates (less than 28 days old) are admitted to the children's ward and the indication for admission. To highlight potentially avoidable causes for neonatal admissions, with a view to reducing them. Methods: We identified our population by comparing our local birth rate, and or neonatal admission rate to the children's ward. Secondly, we audited all neonatal admissions to the children's ward over a 12 week period. We reviewed electronic records and assessed 5 criteria: Reason for admission Source of referral Day of life of admission Duration of admission Whether admission potentially avoidable Results: Our local birth rate is 2, 000 annually. This equates to approximately 450 livebirths over the 12 week period. 32 neonates out of 450 live births during this timeframe were admitted to the children's ward. A hospital admission rate of 7%. Reason for admission: 11 (34%) suspected/confirmed sepsis 10 (31%) jaundice 8 (25%) weight loss 3 (9%) other Source of referral: 17 (53%) community midwives 6 (19%) GP 6 (19%) A&E 3 (9%) other Day of life on admission: 7 (21%) attended within the first 4 days of life 8 (25%) attended on day 5 of life 8 (25%) attended between days 6–15 of life 9 (28%) attended between days 16–28 of life Length of Stay: 8 (25%) stayed 1 night 15 (47%) stayed 2 nights 9 (28%) stayed longer Admission avoidable? 12 (38%) were avoidable 16 (50%) were not avoidable 4 (13%) were not clearly avoidable or unavoidable Conclusion: 7% of babies are admitted to paediatrics in the neonatal period. 38% of admissions were avoidable. Almost all avoidable admissions are breastfed babies admitted with weight loss. Nearly all were referred by the community midwifery team on day 5, co-inciding with newborn blood spot screening. Weight loss >13% was common. All were discharged home within 2 days with a feeding plan. We are now looking at how to support these families in the community to prevent avoidable neonatal admissions to paediatrics. Source of referral: